East Coast Economic Region From The Perspective Of Shift-Share Analysis - Mohd Khairul Hisyam, Hassan; Zakariah, Abdul Rashid; Khalid, Abdul Hamid (Universiti Malaysia Sarawak (UNIMAS), 2011)
The Malaysian government is promoting a new regional development method particularly by promoting a regional development corridor. Our paper tries to examine this new development from the perspective of regional shift-share analysis that covers the period of 2005 – 2007. For that purpose, we compile several data which is subdivided into three different sub-periods, aims at analysing the performance of ECER economy vis-à-vis national economy. The ECER regions GDP data are accordingly collected by its major sectors sourced from the EPU and respective state’s EPU which is expressed in its real value by using the GDP deflator. The results revealed that to investors the ECER regions is unattractive locationally, and its advantage in agriculture, manufacturing, and construction sectors is improved because of structural change at the national level. As an alternative, this study offers a few policy recommendations for investment plans in promising lucrative returns to production and business sectors.